Implementation of Student Management System at TK Al-Wahyu Surabaya - Budi Nugroho; Eka Prakarsa Mandyartha; M. Syahrul Munir (Nusantara Science and Technology Proceedings, 2021)
The School of TK Al Wahyu Surabaya has difficulties in managing student data (especially students registered in the previous few years), so the school management only focuses on the list of students in the current academic year. Data management manually takes a long time, the accuracy of the people who handle it, and is very susceptible to human error. Based on the field survey that has been carried out, school managers have difficulty managing data recorded on papers and computer files, especially when the school has to send report data to the relevant City Government Education Office. Through this community service activity (PIHAT Program), the Proposing Team offers a solution to these problems by implementing the Student Management System at TK Al-Wahyu Surabaya. In this system, student data management is carried out using web-based software to facilitate data gathering, automatic data retrieval, and student data mapping. The activity steps needed to realize the proposed solution include system requirements analysis, system customization, server & network infrastructure preparation, system installation, data entry to the system, training and assistance for system operation, evaluation of problems that arise during system operation, improvement of the system to overcome obstacles that arise and ensure the system can run according to plan, as well as final evaluation to determine the effectiveness of system implementation. Based on the activities that have been carried out, the installation of the application system and the process of assisting school administrators and admins for the operation of the system have been carried out. School administrators are very enthusiastic about implementing this system. This system supports data management and reporting to the City Government Education Office. For TK Al Wahyu Surabaya, the application of this system is a new breakthrough for schools, which have been accustomed to manual work, then use software-based methods that are faster and more effective.